2016
DOI: 10.1186/s13000-016-0492-4
|View full text |Cite
|
Sign up to set email alerts
|

High CHI3L1 expression is associated with glioma patient survival

Abstract: BackgroundSurvival of glioma patients with the same tumor histology and grade can vary significantly, and some low-grade gliomas transform to a more malignant phenotype. There is a need of molecular signatures, which are better predictors of the patient diagnosis, outcome of treatment, and prognosis than the diagnosis provided by histopathology. We propose CHI3L1 mRNA expression as a prognostic biomarker for patients with glioma.MethodsWe measured CHI3L1 expression with quantitative real time-polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…A wealth of clinical evidence has revealed that elevated serum levels of CHI3L1 in GBM are positively correlated with cancer invasiveness, radioresistance, recurrence, and reduced patient survival times [37,38]. There are data that suggest that CHI3L1 expression could be a prognostic predictor of glioblastoma [39,40,41]. This is the same as what we found.…”
Section: Discussionsupporting
confidence: 86%
“…A wealth of clinical evidence has revealed that elevated serum levels of CHI3L1 in GBM are positively correlated with cancer invasiveness, radioresistance, recurrence, and reduced patient survival times [37,38]. There are data that suggest that CHI3L1 expression could be a prognostic predictor of glioblastoma [39,40,41]. This is the same as what we found.…”
Section: Discussionsupporting
confidence: 86%
“…To determine the performance of this online tool, 53 previously published GBM prognostic factors collected as the procedure shown in Figure S1 and then they were evaluated in OSgbm (Table 2, Figure 1) (Sano et al, 1999;Hung and Howng, 2003;Heimberger et al, 2005;Aaberg-Jessen et al, 2009;Shirai et al, 2009;Pu et al, 2011;Cui et al, 2013;De Tayrac et al, 2013;Lee et al, 2013;Rosati et al, 2013;Wang et al, 2013;Wu et al, 2013;Bai et al, 2014;Han et al, 2014;Meng et al, 2014;Olmez et al, 2014;Zupancic et al, 2014;Maris et al, 2015;Moutal et al, 2015;Yan et al, 2015;Zhao et al, 2015;Chaurasia et al, 2016;Nduom et al, 2016;Steponaitis et al, 2016;Steponaitis et al, 2016;Zhang et al, 2016a;Zhang et al, 2016b;Deng et al, 2017;Dong et al, 2017;Ge et al, 2017;Han et al, 2017;Haynes et al, 2017;Huang et al, 2017;Li et al, 2017;Luo and Zhuang, 2017;Ma et al, 2017;Roy et al, 2017;Wu et al, 2017;Zhang et al, 2017;…”
Section: Validation Of Previously Reported Gbm Prognostic Biomarkersmentioning
confidence: 99%
“…After six days of transfection, total RNA was isolated and the transcription levels of PARP6 and survivin were determined by real-time reverse transcriptase polymerase chain reaction (25). The primer pairs were: TTTGAGCCTTATCCC TCTGTG (sense) and TGGGTCATCTCCCGAATAGA (antisense) for PARP6; TTTGAGGAAACTGCGGAGAA (sense) and GGTGGCACCAGGGAATAAA (antisense) for survivin; and primers for β-actin ATCGTGCGTGACATTAAGG AGAAG (sense) and AGGAAGGAAGGCTGGAAGAGTG (antisense).…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
“…The primer pairs were: TTTGAGCCTTATCCC TCTGTG (sense) and TGGGTCATCTCCCGAATAGA (antisense) for PARP6; TTTGAGGAAACTGCGGAGAA (sense) and GGTGGCACCAGGGAATAAA (antisense) for survivin; and primers for β-actin ATCGTGCGTGACATTAAGG AGAAG (sense) and AGGAAGGAAGGCTGGAAGAGTG (antisense). The final result was expressed as log2 of 2 -ΔCT calculation, and the levels of mRNA were normalized to β-actin (25).…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%